Analysis of the Dominant Factors Associated with the Incidence of Covid-19 in Prehospital and Intra-Hospital Nurses - Khotimah, Nur Intan Hayati Husnul; Muslim, Dede Nur Aziz; Puspitasari, Santi; Imam, Haerul (International Journal of Research in Community Services, 2024)
Nurses are the main lead in tackling the Covid-19 pandemic as if they are risking contracted by Covid-19. High stress during a pandemic has an impact on psychological problems, Personal Protective Equipment (PPE) usage, decision-making difficulty on triage, and fatigue in which those can decrease the immune systems. The aim of study was to identify the dominant factors related to the incidence of Covid-19 in nurses. This observational study used Cross Sectional Study design and consecutive sampling techniques at 136 respondents. Questionnaires was used as instruments tested by validity and reliability to measure Fatigue, Psychological Problems (Depression, Anxiety, Stress), Decision-Making Ability of Triage-EWS Screening Covid-19, Vaccination history, risks of exposure, PPE usage and Covid-19 Incidents. Dominant factor analysis was assessed using multivariate analysis by logistic regression test. Based on the results of the logistic regression test, it was found that the risk of exposure to Covid-19 was the dominant factor with the incidence of Covid-19 among nurses in the pre-intra-hospital settings with significance of the test results p value <0.0. Handling of Covid-19 incidents in health workers is crucial. It has been clear that the risk of exposure to people who are confirmed positive can increase the incidence of Covid-19, so it necessary to make prevention program by implementing physical distancing and increasing activities that impact on increasing of immunity.